Towards Understanding When Service-Learning Fosters Efficacy Beliefs of Preservice Teachers - Tice, Kathleen; Nelson, Larry (International Journal of Research on Service-Learning in Teacher Education, 2015)
This research uses a mixed methods approach in focusing upon the role service-learning can play in enhancing preservice teachers sense of efficacy. Results of the quantitative component reveal significant gains in efficacy beliefs of preservice teachers who engaged in a service-learning project during a course in their teacher preparation. At the completion of a service-learning project, preservice teachers shared their perceptions of their participation through written reflections. Qualitative analysis of the preservice teachers written reflections and the characteristics of the service-learning experience uncover sources of efficacy, providing guidance for planning service-learning in teacher education. Additionally, findings document the importance of providing preservice teachers learning experiences that are authentic while also providing ample support for success.